Simulation Study on Internal Short Circuits in a Li-Ion Battery Depending on the Sizes, Quantities, and Locations of Li Dendrites - Kim, Suhwan; Song, Jihun; Lee, Hyobin; Jung, Seungwon; Park, Joonam; Lee, Hongkyung; Lee, Yong Min (Frontiers in Materials, 2022)
Internal short circuit caused by Li dendrite is well known to be a major reason for fire or explosion accidents of state-of-the-art lithium-ion batteries (LIBs). However, post-mortem analysis cannot identify the most probable cause, which is initially embedded in the cell, because the original structure of the cell totally collapses after the accident. Thus, multiphysics modeling and simulation must be a terrific solution to investigate the effect of specific cause in a variety of conditions. Herein, we report an electrochemical-thermal model to simulate the internal short circuit depending on Li dendrite’s size (1, 3, 5, 7 and 9 μm), quantities (1 to 9), relative locations (0, 25, 50, 100, and 150 μm), and external temperature (-10, 10, 30, and 50 ℃). Through monitoring the temperature change affected by the joule and reaction heats for each case, we can suggest critical conditions to lead to unavoidable thermal runaway. Thus, this model can be a steppingstone to understand the correlation between internal short circuits and Li dendrites.